First report of Bacterial Spot with gum production in almond fruits of Argentina - Marangi, María Julia; Temperini, Carolina Virginia; Fernandez, Diana; Pardo, Alejandro Guillermo; Pose, Graciela Noemí (Ediciones INTA, 2020)
Bacterial Spot of Almond is a pathology caused by Xanthomonas arboricola pv. pruni responsible for significant yield losses. During 2017, young symptomatic almond fruits were observed in orchards of Northern Patagonia, Argentina. Symptoms consisted of small watery circular lesions, from which an amber gummy substance emerged. The objective of this work was to determine the etiology of this pathology considering that the symptoms were coincident with those previously described for the bacterial spot with gum production caused by Xanthomonas arboricola pv. pruni on almond fruits in other parts of the world. The presence of Xanthomonas arboricola in damaged fruits was determined confirming their identity by molecular analysis. Symptomatology and gum production were demonstrated by performing pathogenicity tests. As a result, Bacterial Spot with gum production is reported for the first time on almond fruits in Argentina.